A Cosmopolitan Ghetto: The Shifting Image of Kibera Slum From ‘Flying Toilets’ to a Centre for Metropolitan Innovation - John M. Wambui (The Thinker)
It has become customary, when conceptualising twenty-first-century urban landscapes, to describe them as existing in two states. The first state is one in which scholars of modern metropolises conceptualise them as new articulations of social, economic, and political identity.